Evaluating GRI Standards Implementation Quality and Greenwashing Practices in PT Pertamina (Persero) - Wiwik Mukholafatul Farida; Achmad Iqbal; Dwi Rahma Fitriani (Universitas Muhammadiyah Malang, 2026)
Purpose: This study aims to evaluate the application of the Global Reporting Initiative (GRI) standards in the sustainability report of PT Pertamina (Persero) for the 2021-2023 period and analyze the potential for greenwashing practices in the report. Methodology/approach: Utilizing the content analysis method, this study assessed the quality of the report based on GRI principles, both quantitatively and qualitatively. Findings: PT Pertamina (Persero) consistently enhances its sustainability report disclosure quality, with general disclosures reaching 100% over three years. Material topic disclosure is expected to increase from 70% (2021) to 94% (2023). The Greenwashing Index (GI) stabilized at 0.72, indicating low greenwashing levels. Results suggest a strong commitment to transparency and accountability, but ongoing evaluation of greenwashing practices is necessary. Practical implications: This study contributes significantly to understanding the effectiveness of GRI implementation in the Indonesian oil and gas sector and provides recommendations for other companies and regulators to enhance the quality of sustainability reports. Originality/value: This study analyzes the quality of sustainability reports both quantitatively and qualitatively. The researcher also added an analysis of greenwashing practices.